Effects of early-age feed restriction and thermal conditioning on the physiological and performance responses of broiler chickens under heat stress - Aderanti Ifeoluwa Oni; Yusuf Olatunji Bello; Damilola Janet Ibigbami; Christianah Adewumi Ishola; Segun Oluwafemi Adesanya; Daniel Adeyinka Adeniran; Oyegunle Emmanuel Oke (Scientific Reports)
Abstract The perinatal experiences in broiler chickens can have a significant impact on the phenotypes of offspring and can affect how they interact with their environment, affecting their health, productivity and welfare. This study aimed to evaluate the synergistic effect of early-age feed restriction and thermal conditioning on the physiological responses of broiler chickens in hot tropical environments. Two hundred forty male Marshall broiler chicks were assigned to four treatments with four replicates of fifteen birds each. The treatments comprised: broiler chicks raised conventionally (CO), broiler chicks exposed to 60% feed restriction at days 4, 5 and 6 (FR), chicks thermally-conditioned (38 °C) at day 5(TC) for 24 h and broiler chicks subjected to thermal conditioning at (38 °C) at day five and exposed to 60% feed restriction at 4,5 and 6 (TCFR). A completely randomized design was used for the experiment. The results obtained revealed that the final body weights of TCFR chickens were significantly higher (P < 0.05) than TC, which were higher (P < 0.05) than FR and CO chickens. The feed conversion ratio of CO chickens was higher (P < 0.05) than those of TC, FR and TCFR. A higher (P < 0.05)concentration of serum malondialdehyde was recorded in CO chickens than the other treatment groups. Overall, this study has demonstrated that the combination of early feed restriction and thermal conditioning positively affected broiler chickens’ growth performance and antioxidant status in hot tropical environments. The findings of this study suggest that the use of early-age feed restriction and thermal conditioning could be beneficial in alleviating heat stress in broiler chickens.